A survey on the first – year students’ English language learning style preferences at Hanoi University of Business and Technology - Trần, Nam Thiên Hương (University of Languages and International Studies, 2017)
Chapter 1, Literature review, deals with definitions of terms, the origin, background history and categorization of learning styles, students' learning preferences, mismatches between students' learning styles and teachers' awareness of them. The methods of the study adopted as well as justifications for the chosen instruments, participations, data collection and analysis procedure are discussed in chapter 2-Methodology. In the third chapter, the data on two major criteria: the preferred style of acquiring knowledge and information in real life; and the preferred style of acquiring knowledge and information in classroom in terms of learning mode, perceiving and processing information, vocabulary, class activities, teaching aids, error correction and feedback are presented. This chapter points out the results combined with critical interpretation and analysis, from which major findings are revealed and discussed.